VISI KEPALA SEKOLAH SEBAGAI PENGGERAK MUTU PENDIDIKAN - Harapan, Edi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
The low quality of school was based on the role of teachers and headmaster. The leadership of headmaster is an important one to upgrade the quality of school. To improve the quality education, the headmaster should have a clear vission which is oriented to the quality of school. The continuous professional development of headmaster should be applied. The professional headmaster will understand the needs of education. Through the vission of headmaster as the operator of education will solve the low quality of school.Â Keyword: Leadership, Headmaster, Vission, Quality of School.